Antibodies in the breast milk of a maternal woman with COVID-19 - Yunzhu Dong; Xiangyang Chi; Huang Hai; Liangliang Sun; Mengyao Zhang; Wei-Fen Xie; Wei Chen (Emerging Microbes and Infections, 2020)
ABSTRACTA maternal woman was positive for SARS-CoV-2 tested in throat swabs but negative tested in other body fluids, and she had IgG and IgA detected in breast milk. Her infant negative for SARS-CoV-2 at birth had elevated IgG in serum but quickly decayed. These findings suggest that breastfeeding might have the potential benefit to the neonates.